The removal of antibiotics in water by chemically modified carbonaceous adsorbents from biomass: A systematic review. (15th May 2023) - Anuar, Nur Faradila; Iskandar Shah, Darween Rozehan Shah; Ramli, Fitri Fareez; Md Zaini, Mohd Saufi; Mohammadi, Nasrin Agha; Mohamad Daud, Ahmad Rafizan; Syed-Hassan, Syed Shatir A.
Abstract: Antibiotics are extensively used in treating infectious diseases for both humans and animals. However, they are generally not fully digested in the body and are released as active compounds into aquatic systems through domestic sewage treatment plants, where they can cause chronic toxicity and some potentially major health and environmental risks. Many researchers reported that conventional wastewater treatment processes cannot completely eradicate antibiotic residue and that these residues may be discharged to the receiving rivers and streams. Adsorption was claimed to be able to remove these contaminants even at low concentrations and under a variety of pH conditions. Biomass-based adsorbent materials have recently been used to remove antibiotics due to their wide availability, eco-friendly nature, good surface characteristics, and low cost. This study conducted a systematic review of biomass-based carbon adsorbents used for antibiotic removal. The surface chemistry and maximum antibiotic adsorption capacities were reviewed and discussed based on the type of biomass and chemical modification. The effect of influential variables such as pH, initial concentration of antibiotics and adsorbent dosage was also discussed in detail. After the screening process, four articles were found to be suitable for the detail analysis on reusable efficiency. Results of the detail analysis shows coconut shell and sawdust based-carbon adsorbent could remove antibiotics with 89% reusable efficiency after the fourth cycle of reuse. Overall, this systematic review ascribes the research work for synthesizing an excellent performance of biomass-based carbon adsorbent. Highlights: A systematic review on chemically modified biomass-based carbon adsorbent for the removal of antibiotics in water. The performance of carbon adsorbent depends on the chemical and physical properties of the adsorbent surface. Chemical modification is effective to enhance adsorption capacity for antibiotics removal. Reusable efficiency of 89% is possible after four cycles of antibiotics removal.